READER TRAINING: EXPERIENCES OF READING, PLEASURES AND DISCOVERIES THAT ENHANCE WRITTEN PRODUCTION - Elza Ferreira Santos; Sônia Pinto de Albuquerque Melo; Cyndi Moura Guimarães de Oliveira (Universidade Federal de Sergipe, 2018)
In a country bonded statistically by non-readers, this study aimed to re ect on the process of training of readers. For this purpose, the research published in Portraits of Reading in Brazil (2008) was used as theoretical reference. e research showed that the methodological practices adopted with 4th grade classes in Portuguese Language classes at the Federal Institute of Sergipe (IFS), Campus Aracaju, consider the conception of polytechnic and omnilateral education (FRIGOTTO, 2001; SILVA, 2000) of that educational institution. e action research revealed the possibility of forming a culture of reading, in addition to provoking a repertoire for the acquisition of the habitus of reading.